Use of the Poisson log-linear model for the study of homicides against young nicaraguan immigrants in Costa Rica - Bonilla, Roger E. (Población y Salud en Mesoamérica, 2016)
Objective: To describe the homicides rate for young Nicaraguan immigrants in Costa Rica. Methods: We used a Poisson log-linear regression model at small administrative areas-level to describe the homicides rate for young Nicaraguan immigrants in Costa Rica, given the co-variables (Agresti, 2002; Cameron y Trivedi, 1998; Neter, Wasserman, Kutner & Nachtsheim, 1996). Results: Incidence rate for percentage of poor households, percentage of adults 35 years-old and more, and the percentage of the population on the service sector of the economy are 1.04, 1.05 and 1.05 respectively. Conclusions: Poverty, population structure and economic activities of the service sector of the economy are the co-variables that best describe the homicides rate for young Nicaraguan immigrants in Costa Rica.